2013
DOI: 10.1161/hypertensionaha.111.00682
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime Blood Pressure and New-Onset Left Ventricular Hypertrophy

Abstract: Extensive echocardiographic investigations performed in the past 3 decades have shown that hypertensive heart disease includes a variety of anatomic and functional alterations, such as left ventricular hypertrophy (LVH), systolic/diastolic dysfunction, myocardial fibrosis, and left atrial and aortic dilatations. [1][2][3][4][5] Among these manifestations of cardiac damage, particular attention has been devoted to LVH because this phenotype has been reported to be a powerful, independent predictor of cardiovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 39 publications
(29 reference statements)
4
32
0
1
Order By: Relevance
“…Nighttime BP, in particular systolic values, has been described as an independent predictor of new-onset LV hypertrophy in the general population. 27 In animal models of sinoaortic denervation, characterized by normal BP values and high BP variability, the activation of different mechanosensitive and autocrine pathways mediates cardiac hypertrophy in response to mechanical stress. 28 In our study, LVMi was related to mean 24-hour BP values, and both 24-hour and nighttime SBP were predictors of organ damage in the whole study population independent of indexes of BP variability.…”
Section: Hypertrophymentioning
confidence: 99%
See 1 more Smart Citation
“…Nighttime BP, in particular systolic values, has been described as an independent predictor of new-onset LV hypertrophy in the general population. 27 In animal models of sinoaortic denervation, characterized by normal BP values and high BP variability, the activation of different mechanosensitive and autocrine pathways mediates cardiac hypertrophy in response to mechanical stress. 28 In our study, LVMi was related to mean 24-hour BP values, and both 24-hour and nighttime SBP were predictors of organ damage in the whole study population independent of indexes of BP variability.…”
Section: Hypertrophymentioning
confidence: 99%
“…Se ha comunicado que la PA nocturna, en particular los valores sistólicos, es un factor predictivo independiente de aparición de hipertrofia VI en la población general. 27 En modelos animales de desnervación sinoauricular, caracterizada por valores de PA normales y alta variabilidad de la PA, la activación de diferentes vías mecanosensitivas y autocrinas media la hipertrofia cardíaca en respuesta a esfuerzo mecánico. 28 En nuestro estudio, la MVIi se relacionó con los valores medios de PA de 24 horas, y tanto la PAS de 24 horas como la PAS nocturna fueron factores predictivos de lesión orgánica en toda la población de estudio, independientemente de los índices de variabilidad de la PA. Estos resultados avalan la hipótesis de que, en la INV, la relación entre PAS de 24 horas y MVIi no depende de la variabilidad de la PA, lo que coincide con un estudio previo.…”
Section: Hipertrofia Ventricular Izquierdaunclassified
“…A blunted, or absent, nocturnal fall in BP, reflecting a disrupt circadian rhythm, is considered a powerful risk factor for asymptomatic organ damage and cardiovascular events in a variety of clinical settings; nocturnal BP has been also shown to be a better predictor of cardiovascular events than 24 h or daytime BP [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…With respect to BP, a recent meta-analysis concluded that a higher nighttime BP is a better predictor for adverse outcome than a higher day-time BP or even a low day-night BP ratio. [15] Specifically a high night-time BP rather than day-time BP is associated with chronic kidney disease, [16] left ventricular hypertrophy [17] and cardiovascular disease. [18][19][20] Cuspidi and Grassi [21] conclude that nocturnal BP should be targeted by treatment.…”
Section: Discussionmentioning
confidence: 99%